ANALISIS PENGARUH TATA KELOLA PERUSAHAAN TERHADAP MANAJEMEN LABA - Mahendra Taufiq Noviardhi; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the effect of corporate governance on earnings management in manufacturing companies. Corporate governance is seen in the study of boards of directors, board of directors, ownership structure, audit committee, firm size, and leverage. Ownership structure used in this study is the family ownership structure in which companies with family ownership does not belong to the public, government, and foreign. Firm size was measured by using the total assets owned by the company. This research was done by taking the data from the Indonesian Capital Market Directory (ICMD) and the financial statements of manufacturing company. The method of analysis used in this study is multiple regression. The population which used in this research is manufacturing company which listed in Indonesian Stock Exchange . The sample which used in this research is 50 companies which listed on Indonesian Stock Exchange on 2009-2011. The results of this study indicate that the firm size variable has a significant effect on earnings management. The only variable that showed a negative relationship is board of directors, it’s mean that the board looks have didn’t make earning management.